Report of the Delhi Improvement Trust Enquiry Committe 1951 Vol 1 - Planning Commission (Planning Commission, 1951)
The death on October 26, 1950 of Shri Amar Nath Nanda, one of the Members, before the report could bo finalised deprived the Committee of his valuable services. It was a serious loss, us the. Committee had relied to a considerable extent on his administrative experience and shrewd judgment in tho earlier stages of its inquiry. Another Member, Shri B. Shiva Rao, was nominated by the Government of India ns u delegate to tho U. N. General Assembly. He was, therefore, compelled to be absent from the meetings of the Committee after the 29th July 1950, and rejoined it early in January 1951.
Government of India Ministry of health